2016
DOI: 10.1016/j.seizure.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Tracking generalized tonic-clonic seizures with a wrist accelerometer linked to an online database

Abstract: Automatic detection and recording of GTCS to an online database is feasible and may be more informative than seizure logging in a paper diary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 20 publications
3
61
0
Order By: Relevance
“…More recent studies demonstrated detection sensitivity ranging from 90 to 92% for convulsive seizures [15, 16], but the false positive events varied between the studies. One study reported 40 false alarms in 16 out of 73 patients [15], and another study found 81 false alarms reported in 17 patients out of a sample of 30 [16].…”
Section: Resultsmentioning
confidence: 99%
“…More recent studies demonstrated detection sensitivity ranging from 90 to 92% for convulsive seizures [15, 16], but the false positive events varied between the studies. One study reported 40 false alarms in 16 out of 73 patients [15], and another study found 81 false alarms reported in 17 patients out of a sample of 30 [16].…”
Section: Resultsmentioning
confidence: 99%
“…A study of the Epi‐Care system developed by Danish Care Technology ApS demonstrated a sensitivity of 89% for detection 39 GTCS in 20 patients in the EMU with a FAR of 0.2 per 24 h 16. A recent study of the SmartWatch system being developed by SmartMonitor, reported that the device detected 12 of 13 GTCS (92.3%) in nine patients in the EMU with 81 FAs (with the FAR not detailed) 17. A previous study of the SmartWatch had shown only a 31% sensitivity for detecting GTCS (with the FAR not reported) 18.…”
Section: Discussionmentioning
confidence: 99%
“…Another important limitation of this study is that analyses were done retrospectively, differently from above-mentioned studies with real-time analysis 13,15,18,19,39 . Based on the robust cross-validation approach on a large number of CSs and on our simulated real-time processing, our expectation is that performance of an algorithm embedded in a real-time system will not change significantly (as verified by preliminary tests underway).…”
Section: Limits and Future Workmentioning
confidence: 99%